Bacterial Flora Isolated From Dried Fishes Sold at Retail Markets Within Dhaka City Corporation of Bangladesh - Hassan, Md Kamrul; Poppy, Munalisa; Ahamed, Tanvir; Morsheda, Fahima; Yadav, Ravi; Hasan, Alamgir; Siddique, Mahbubul Pratik (Research in Agriculture Livestock and Fisheries, 2021)
Along with other contaminants, bacterial contamination in the dried fishes is a common issue which severely affects the quality of cured fishes. Hence, the present study was aimed to isolate and identify different bacterial flora contaminating different dried fishes, sold at different retail markets within Dhaka Metropolitan city, Dhaka, Bangladesh. A total of 25 different dried fishes were collected from Dhaka North city corporation area (Town Hall kacha bazar, Krishi market, and Mohammadpur kacha bazar) and Dhaka South city corporation area (New market kacha bazar, and Jatrabari chowrasta bazar). Each sample was divided into three regions (head, body, and tail) and bacterial isolation and identification was done by studying their cultural, staining and biochemical properties. Of the 25 dried fishes, Escherichia coli, Bacillus spp., Staphylococcus spp., Salmonella spp. and unidentified bacteria isolation rates were 44%, 56%, 80%, 48%, and 24%, respectively. The presence of E. coli and Salmonella spp. in various dried fish samples could be considered as indication of lack of hygienic condition during dried fish processing. Confirmation through molecular detection methods, pathogenicity, and antibiogram of the isolated bacteria could be included for future study. Res. Agric., Livest. Fish.8(1): 109-115, April 2021